EDUKASI DAN SCRENING PADA IBU HAMIL TENTANG DIABETES MELITUS GESTASIONAL DI KELURAHAN SAWA KABUPATEN KONAWE UTARA - Aswita; Yulita, Hendra; Dolofu, Muliati; Hikmandayani, Hikmandayani (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2024)
The impact of complications arising from gestational diabetes mellitus such as increased SC deliveries, macrosomia, preeclampsia, hypoglycemia, premature birth and others (RSCM, 2017). The prevalence of Pregnancy DM is increasing, especially in developing countries, estimated at 3.8% to 21%. The prevalence of DM complications in Indonesia is 2 out of 5 diabetic women in the reproductive age range. The impact caused by mothers suffering from gestational diabetes mellitus is that the mother is at high risk of excess weight gain, preeclampsia, eclampsia, caesarean section, and cardiovascular complications and even maternal death. Educational Objectives Health education is carried out for pregnant women to increase knowledge and it is hoped that efforts will be made to prevent the disease. The education methods provided are in the form of counseling and health checks including blood pressure checks, anthropometry and blood glucose as well as health education. Health education provided regarding danger signs and risk factors for pregnant women regarding Gestational Diabetes Mellitus Results. Measurement of mothers' knowledge about the introduction of gestational diabetes mellitus resulted in the average value of knowledge of pregnant women during the pretest being 60.00 (good enough category according to Arikunto), all participants experienced an increase in knowledge with an average of 90.00 (good category according to Arikunto ). Conclusion: By providing education to pregnant women about gestational diabetes mellitus smoothly, there is an increase in understanding of pregnant women about gestational diabetes mellitus.Keywords: Hypertension, Cadre, Pregnancy, Preeclampsia.